Research and application of industrial data acquisition based on industrial internet of things - Jianxiong ZHANG; Xiaoli WU; Zhen YANG; Jie LI (Dianxin kexue)
IoT application scenarios and technology in the field of industrial data acquisition were analyzed,including the current situation and problems analysis of industrial data acquisition,typical application scenario and technology characteristics of industrial data acquisition,and cloud network integration technology research with telecom operators.The technical architecture and corresponding solutions of industrial data acquisition for telecom operators were put forward.It can be widely used in remote monitoring and intelligent maintenance application for various industrial equipment or intelligent products,and can realize preventive maintenance and performance optimization analysis.